Employment in crisis : the path to better jobs in a post-COVID-19 Latin America - Silva, Joana; Sousa, Liliana D.; Packard, Truman G., 1972-; Robertson, Raymond (Professor of economics and government) (World Bank Latin American and Caribbean studies., 2021)
"A better policy framework for preventing, managing, and helping people recover from crises is crucial to lifting long-term growth and livelihoods in Latin America and the Caribbean (LAC). The need for this policy framework has never been more urgent as the region faces the monumental task of recovery from the worldwide COVID-19 pandemic. Whether specific policy responses will deliver the expected growth dividends will depend on the underlying vision of how labor markets adjust to crises and the quality of the policies enacted. This report estimates how crises change labor market flows, assesses how these changes affect people, and discusses the key policy responses"--